ARUS URBANISASI DAN SMART CITY - Yusriani Sapta Dewi (PROSIDING, 2022)
Urbanization is a major phenomenon in urban development and is a natural phenomenon in line with economic development and the level of welfare of the population in a country. Increased urban population growth will cause various problems and bring consequences in all aspects of urban life including various positive and negative impacts. . Rapid urban population growth, it is difficult to follow the capacity of the city's carrying capacity. Cities with population growth will bear more complex problems; While natural resources and energy are increasingly limited. So far, the various solutions offered are conventional and not quick in responding to more and more problems. In order for urban development to be sustainable, solutions need to be done. Smart city is a solution to meet expectations and minimize the impact of urbanization.